Factors Associated with Sodomy Cases at a Tertiary Care Hospital of Karachi - Abdul Waheed; Mir Ghulam Ali Talpur; Iqbal Ahmed Khan; Hari Ram; Shahid Nezam; Syed Pervaiz Alam (Journal of Bahria University Medical and Dental College)
Objective: To observe the number of sodomy cases and their associated factors reported to Abbasi Shaheed Hospital for medicolegal examination in Karachi. Study design and setting: The retrospective study design conducted at medicolegal section of Abbasi Shaheed Hospital Karachi from January 2016 till December 2018 reported from 45 different police stations of Karachi. Methodology: This was a single centred study on sodomy conducted by using non-probability sampling technique. Data was collected from medico legal section of Abbasi Shaheed Hospital, Karachi, from a period of January 2016 till December 2018 reported from 45 different police stations of Karachi. Results: A total of 102 sodomy cases were reported in various police stations of Karachi during this period. Majority of cases were reported in the police stations belonging to Surjani town (11) followed by Sir Syed (9), Sohrab Goth (9), North Naziamabad (8) and Gulbahar (7). Majority of the convicts belonged to the age range 21-30 years followed by 10-20 years of age. Majority of the accused were found to be living alone without family for earning purpose. All of them were usually of poor socio economic conditions and illiterate. Majority of the couples were found to be related to each other. Presence of semen stains, sexual potency and DNA analysis further confirmed their involvement. Conclusion: Majority of the accused were of young age, poor, living alone without family, illiterate and from laborer class. These might be the factors responsible for their involvement in alleged sexual behavior.